2012
DOI: 10.1016/s1470-2045(12)70004-9
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of T-cell-epitope matching at HLA-DPB1 in recipients of unrelated-donor haemopoietic-cell transplantation: a retrospective study

Abstract: Summary Background The risks after unrelated-donor haemopoietic-cell transplantation with matched HLA-A, HLA-B, HLA-C, HLA-DRB1, HLA-DQB1 alleles between donor and recipient (10/10 matched) can be decreased by selection of unrelated donors who also match for HLA-DPB1; however, such donors are difficult to find. Classification of HLA-DPB1 mismatches based on T-cell-epitope groups could identify mismatches that might be tolerated (permissive) and those that would increase risks (non-permissive) after transplanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
344
8
12

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 320 publications
(389 citation statements)
references
References 33 publications
(60 reference statements)
25
344
8
12
Order By: Relevance
“…We further analyzed HLA-DPB1 mismatches through their classification into permissive vs nonpermissive, according to their belonging to different T-cell epitope groups. 36 Although, as previously reported, HLA-DPB1 nonpermissive mismatches were associated with an increased incidence of acute GVHD III-IV and NRM (supplemental Table 5), they did not affect our conclusions (ie, the effect of MICA mismatches on acute GVHD III-IV, chronic GVHD, relapse, and NRM; supplemental Table 5). Finally, we found no association of mismatches at MICA amino acid position 129 (known to affect binding affinity for NKG2D) with any of the tested clinical endpoints (supplemental Table 6).…”
Section: Resultssupporting
confidence: 56%
“…We further analyzed HLA-DPB1 mismatches through their classification into permissive vs nonpermissive, according to their belonging to different T-cell epitope groups. 36 Although, as previously reported, HLA-DPB1 nonpermissive mismatches were associated with an increased incidence of acute GVHD III-IV and NRM (supplemental Table 5), they did not affect our conclusions (ie, the effect of MICA mismatches on acute GVHD III-IV, chronic GVHD, relapse, and NRM; supplemental Table 5). Finally, we found no association of mismatches at MICA amino acid position 129 (known to affect binding affinity for NKG2D) with any of the tested clinical endpoints (supplemental Table 6).…”
Section: Resultssupporting
confidence: 56%
“…11 However, in a 2012 retrospective analysis of nearly 12 000 HCTs using high-resolution HLA typing, Petersdorf et al showed that HCT transplants with HLA-DPB1 non-permissive mismatching, as defined by T-cell epitope cross-reactivity groups, are significantly associated with poorer TRM in 10/10 and 9/10 MUD-HCT. 12 Similar studies on other classically 'low-expression' HLAs (including HLA-C, DQ and DR51/52/53) have also recently been shown to affect transplant outcome. 13,14 These findings underscore the value of large-scale longitudinal analysis, the use of molecular and sequence-based HLA typing, and the increasing importance of nonclassical HLA genes in HCT outcome as most allogeneic HCTs are now fully or near-fully HLA matched.…”
Section: Box 1 New Genomics Technology In Hctmentioning
confidence: 78%
“…11 As a complement to WES, capture amplicon sequencing (CAS) allows high-throughput, deep resequencing of custom-selected genomic regions (eg, custom panels of genes encoding drug metabolism enzymes). 12,13 CAS exceeds the sensitivity of Sanger sequencing and is particularly useful for heterochimerism detection. For example, a mutation in a single cancer cell among a population of hundreds of normal cells can be identified using CAS.…”
Section: Box 1 New Genomics Technology In Hctmentioning
confidence: 99%
“…The main requirement for selection of an unrelated donor is well recognized to be one who is a match at 10/10 (or 8/8) HLA alleles. 20,21 Selecting a donor based on secondary selection donor characteristics, such as donor age 22 or other (non-classic HLA) genetic factors, [23][24][25] can further enhance outcomes.…”
Section: Discussionmentioning
confidence: 99%